Anti-Müllerian hormone beyond an ovarian reserve marker: the relationship with the physiology and pathology in the life-long follicle development - Iwase, Akira; Hasegawa, Yuko; Tsukui, Yumiko; Kobayashi, Mio; Hiraishi, Hikaru; Nakazato, Tomoko; Kitahara, Yoshikazu (Frontiers in Endocrinology, 2023)
Anti-Müllerian hormone (AMH), an indirect indicator of the number of remaining follicles, is clinically used as a test for ovarian reserve. Typically, a decline suggests a decrease in the number of remaining follicles in relation to ovarian toxicity caused by interventions, which may implicate fertility.In contrast, serum AMH levels are elevated in patients with polycystic ovary syndrome. AMH is produced primarily in the granulosa cells of the preantral and small antral follicles. Thus it varies in association with folliculogenesis and the establishment and shrinking of the follicle cohort. Ovarian activity during the female half-life, from the embryonic period to menopause, is based on folliculogenesis and maintenance of the follicle cohort, which is influenced by developmental processes, life events, and interventions. AMH trends over a woman's lifetime are associated with in vivo follicular cohort transitions that cannot be observed directly.